2021
DOI: 10.3126/jcmsn.v17i2.34328
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice regarding Prevention and Control of COVID-19 among Nurses of Tertiary Care Hospital

Abstract: Background: COVID-19 has become a global health threat and the disease burden is expected to increase more. Nurses are the front lines of COVID management. Because this work requires close personal exposure to patients with COVID-19, nurses are at high risk of infection, contributing to further spread. Nurses’ knowledge, attitudes, and practices can influence the prevention and control of pandemic. Thus, the aim of the study was to assess knowledge, attitude, and practice regarding the prevention and control o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
1
1
1
Order By: Relevance
“…All most all respondents (97.0%) in this study provided correct response for the mode of transmission. This finding was consistent with the study result in Indonesia 9 (95.8%) and nearly consistent with another study findings 81%, in Nepal 7 but contradicted with the study findings of Iran (56.5%). 4 The gold standard test for COVID-19 is PCR.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…All most all respondents (97.0%) in this study provided correct response for the mode of transmission. This finding was consistent with the study result in Indonesia 9 (95.8%) and nearly consistent with another study findings 81%, in Nepal 7 but contradicted with the study findings of Iran (56.5%). 4 The gold standard test for COVID-19 is PCR.…”
Section: Discussionsupporting
confidence: 88%
“…The study showed that only 15.2% of the participants had got COVID 19 related training. This finding was inconsistent with other studies conducted in China (64.6%) 1 and Nepal (89.4%), 7 respectively. It might be due to the difference in the study population; this study was conducted 8 and in Indonesia 85.6%.…”
Section: Discussioncontrasting
confidence: 73%
“…This result is consistent with a study conducted in Nepal in which nurses had a positive attitude about COVID-19 prevention and control measures. 9 In addition, a study in Nigeria found that healthcare workers, including nurses, used preventive measures to reduce the risk of COVID-19 infection. 10 Moreover, in Saudi Arabia, the majority of nurses employed personal protective methods.…”
Section: Resultsmentioning
confidence: 99%